2020
DOI: 10.1088/1681-7575/abbcc0
|View full text |Cite
|
Sign up to set email alerts
|

Spaceborne radiance temperature standard blackbody for Chinese high-precision infrared spectrometer

Abstract: As a radiance temperature standard source for the Chinese high-resolution spectrum infrared spectrometer, the National Institute of Metrology, China, developed a spaceborne radiance temperature standard blackbody (SRTSB) combined with a series of miniature phase change fixed points (MPCFPs) for temperature calibration and emissivity verification using a thermal radiation loop (TRL). The MPCFPs of the SRTSB contain H2O, Ga, Ga–Sn alloy, and phenyl salicylate. The TRL is used to measure the emissivity of the spa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 39 publications
0
1
0
Order By: Relevance
“…Experiments were conducted on the International Space Station with the ITS-90 standard material Ga, and it was found that within a few mK of uncertainty, no significant difference was observed between the melt temperature of the Ga at 1 g and in microgravity. Hao Xiaopeng et al [11,12] studied the fixed point phase change plateau of Ga and Ga-In alloys and showed that the melting point temperature of the Ga and Ga-In alloy fixed point had a good linear relationship with the heating power. Additionally, the phase-change temperature plateaus of six types of miniature fixed points, namely, H2O, Ga-Sn, Ga-Zn, PS, succinonitrile, and Ga, were tested.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments were conducted on the International Space Station with the ITS-90 standard material Ga, and it was found that within a few mK of uncertainty, no significant difference was observed between the melt temperature of the Ga at 1 g and in microgravity. Hao Xiaopeng et al [11,12] studied the fixed point phase change plateau of Ga and Ga-In alloys and showed that the melting point temperature of the Ga and Ga-In alloy fixed point had a good linear relationship with the heating power. Additionally, the phase-change temperature plateaus of six types of miniature fixed points, namely, H2O, Ga-Sn, Ga-Zn, PS, succinonitrile, and Ga, were tested.…”
Section: Introductionmentioning
confidence: 99%